Ampliación del área de distribución de Anthurium atramentarium Croat & Oberle (Araceae) en Colombia y comentarios sobre las especies de Anthurium de espata negra (2014)
The distribution of Anthurium atramentarium in Colombia is expanded, this specie had been reported as endemic from Antioquia department. The necessity to develop strategies to protect species of Anthurium with black spathe that are distributed in Colombia is mentioned.